RESEARCH AND EXPERIMENTAL DETERMINATION OF THERMO PHYSICAL PROPERTIESOF HIGHLY FOAMING SOLUTION - Xalikovna, Musaeva Rano (International Journal of Psychosocial Rehabilitation, 2020)
In the article discusses about basic properties of licorice root, and also, by experimental method, the basic thermophysical characteristics of licorice root are determined.